MOBILIDADE ACADÊMICA INTERNACIONAL EM MOÇAMBIQUE: APRENDIZADOS E PARTILHAS - Pacheco Andrade, Grazielle; Mota Dias, Ludmilla; Silva Oliveira , Carlos Vitor Silva Oliveira (Simpósio Internacional da ARInt: Diálogos Sem Fronteiras, 2026)